Digital Dissertations in the United Kingdom - Matheson, Ann (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
In the United Kingdom a user wishing to consult a UK thesis has traditionally had the following choices: the thesis may be consulted in the Library of the Higher Education Institution (HEI) to which it was submitted; the thesis may be borrowed from the library of the HEI; a copy of the thesis may be purchased form the library of the HEI; the thesis may be borrowed through inter-library loan; or the thesis may be made available through the British Library’s British Thesis Service, which was set up in 1971. This Service currently holds more than 150,000 UK theses, which are added to at a rate of around 7,000 a year, with the participation of about a hundred Higher Education Institutions (HEIs). With the development of new technology, however, an interest developed in examining the feasibility of making theses available online to users. In the United Kingdom, the University Theses Online Group (UTOG) was established as a consequence of a proposal to the Follett Implementation Group on Information Technology in 1994. The University Theses Online Group (UTOG) is a working group of UK university librarians: the Group’s aims are to investigate the technical, cultural and administrative issues associated with the storage and delivery of theses in online form. The Group is made up of representatives of the British Library Document Supply Centre (BLDSC), British Thesis Service, and the university libraries of Cranfield, Edinburgh, Glasgow, Leeds, Manchester, Plymouth, Robert Gordon, University College London, Kent, University of London and Warwick.